Penggabungan Konsep Web 2.0 dan Mashup dalam Pembuatan Situs Dinas Kebudayaan dan Pariwisata Provinsi DKI Jakarta - Bayu Kanigoro; Jurike V Moniaga; Rhezandra Priatama; Konrad Bangun Pratomo; Dimas Eko Adityo (ComTech: Computer, Mathematics and Engineering Applications, 2011)
This study aims to design a website of the Jakarta regional office of Culture and Tourism by combining the concept of web 2.0 and mashup. This concept combines several APIs (Application Programming Interface) into a new application. The APIs used are Facebook, Google Maps, Twitter, and Yahoo Weather. The created site applies the latest technology and advanced multimedia elements. With the combination of all elements above, a more interactive and dynamic site is succesfully obtained.